Characterization of rotaviruses causing diarrhoea in Vietnamese children. - Landaeta, M; Dove, W; Vinh, H; Cunliffe, N; Campbell, J; Parry, C; Farrar, J; Hart, C (2003)
Faecal samples from 123 children admitted to the Centre for Tropical Diseases in Ho Chi Minh city, Vietnam, with acute watery diarrhoea were screened by negative-stain electron microscopy for viral enteropathogens. In addition to the 48 children who were found to be infected with rotavirus only, one had both rotavirus and astrovirus, two had adenovirus 40/41, and one had astrovirus only. The rotaviruses were subjected to molecular analysis by electropherotyping, G- and P-genotyping (by reverse-transcriptase PCR), and amplicon sequencing. By use of newly designed PCR primers, all 49 isolates could be G-genotyped and all but one P-genotyped. Novel variants of G1-G1*--were the most commonly detected G-genotype and such variants of P[8]-P[8*]--were the second commonest P-genotype. The P[8*] and G1* amplicons were, respectively, only 92%-93.4% and 88.1%-89% similar to the corresponding sequences from the prototype P[8] G1 rotavirus, Wa. Several unusual P- and G-genotype combinations were detected. Four (8%) of the children investigated were each found to be co-infected with two different rotaviruses. These data add to our knowledge of the continuing evolution and diversity of human rotaviruses, and should help in the rational design of vaccines.